Implementasi Kaidah al-á¸ŒarÅ«rÄt TubÄ«á¸¥u al-Maá¸¥zÅ«rÄt pada Tindakan Persalinan Operasi Caesar - Sri Kurniawaty Fazriyani Nurdin; Dewi Indriani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
The major objective of this research was to investigate and understand the â€˜Implementation of the Islamic law of al-á¸ŒarÅ«rÄt TubÄ«á¸¥u al-Maá¸¥zÅ«rÄt in a Caesarean deliveryâ€™. The methodological approach taken in this study was a qualitative method by using a grounded research. In terms of the research approach, normative (Fiqh) approach was employed by the researcher. The results of this research indicated that based on medical and Islamic perspective, the practice of caesarean section on a delivery could be done only in an emergnecy situation. In this case, the medical staff should understand the condition of their patients whether or not they could be treated with a caesarean section. Similarly, in terms of the Islamic perspective, the level of an emergeny condition has to be decided by doctors or the medical staff. The caesarean section could only be taken if the surgery is necessary for delivery patients.